Syria: development and monetary policy - Asfour, Edmond Y. (Harvard University Press, Cambridge, Massachusetts, 1959)
The book is a study carried out to ascertain the interplay between monetary changes and the process of economic growth and development in one underdeveloped country of the Middle East, namely Syria.
Bibliographical references included in "Notes": p. [128]-158.
usc 17/07/17
Loans
Keywords: Currency question; Syria